Assistant nurses and orientation to care robot use in three European countries - Tuisku, Outi; Johansson-Pajala, Rose-Marie; Hoppe, Julia Amelie; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten; Gustafsson, Christine; Melkas, Helinä (Behaviour & Information Technology)
Keywords: Human-Computer Interaction; General Social Sciences; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Fallbeschreibungen im Vergleich: Ähnlichkeiten, Widersprüche, Spannungsfelder - Meyer-Hamme, Johannes; Chmiel, Cornelia; Spielhaus, Riem (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Geschichten im Wandel. Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft – Problemaufriss und Konzeption des Bandes - Meyer-Hamme, Johannes; Georgi, Viola; Lücke, Martin; Spielhaus, Riem (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Methodisches Vorgehen - Meyer-Hamme, Johannes; Spielhaus, Riem; Georgi, Viola; Lücke, Martin; Bischoff, Sebastian; Chiriac, Christine; Chmiel, Cornelia; Freund, Sina; Kahle, Lena (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Geschichtskultureller Wandel aus der Perspektive von Akteur:innen non-formaler Bildung - Meyer-Hamme, Johannes; Bischoff, Sebastian (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Erinnerungspraktiken und historisches Lernen - Meyer-Hamme, Johannes; Chmiel, Cornelia (Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft)

Schülerwissen in der geschichtsdidaktischen Forschung - Meyer-Hamme, Johannes (Handbuch Theorie und Empirie der Geschichts- und Politikdidaktik)

Geschichte im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft

Protonation-induced charge transfer and polaron formation in organic semiconductors doped by Lewis acids - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (RSC Advances)
Lewis-acid doping of organic semiconductors (OSCs) opens up new ways of p-type doping and has recently become of significant interest.
Keywords: General Chemical Engineering; General Chemistry

Opportunistic UAV Relaying for Urban Vehicular Networks - Hardes, Tobias; Sommer, Christoph (17th IEEE/IFIP Conference on Wireless On demand Network Systems and Services (WONS 2022))
We study the impact of employing Unmanned Aerial Vehicles (UAVs) flying random, arbitrary missions as purely-opportunistic relays for cooperative awareness applications in vehicular networks. We do not require that opportunistically relaying UAVs alter trajectory nor speed, so that the additional relaying task can be executed with close-to-zero impact on the execution of the primary mission. Based on extensive computer simulations we demonstrate that, within a wide band of acceptable speeds, flight routes (up to a standard deviation of 300 m from the optimum), as well as altitudes, opportunistic relaying of transmissions via UAVs can yield a benefit to system performance that is on the same order of magnitude as that of optimally deployed UAVs. Moreover, much of the reduction in impact due to suboptimal missions can be recovered simply by moderately increasing the number of UAVs.